Membangun Kepemimpinan Kristen Tranfromnasional di masa pandemic Covid-19: Membangun Kepemimpinan Kristen Tranfromnasional di masa pandemic Covid-19 - Purim Marbun; Efesus Suratman; Muryati Muryati Muryati; Yusak Setianto (CARAKA: Jurnal Teologi Biblika dan Praktika, 2022)
Abstract The pandemic period provides various kinds of impacts, one of which is the impact on the leadership aspect. Changes in the situation can affect the leadership process, with this problem the church needs to have a strategy in dealing with this. Appropriate responses and changes are needed to offset the impact of the pandemic. It is in this changing situation that Transnational Christian leadership is needed. The purpose of this research is so that Christian leaders can be built in times of this Pandemic. The research method used in this research is descriptive qualitative. To obtain the necessary data through a literature review for transformative leadership. From this research, the results were found, namely by building leadership that is Transnational Christian Leadership during the Covid-19 pandemic, it has an influence on those who are led to remain confident and confident, always optimistic and have an attitude of helping each other during this pandemic. The people they lead are expected to be more confident and optimistic to optimize their potential, as well as develop other abilities to be able to survive through difficult situations.